Phylogenetic Insights into Chinese Rubus (Rosaceae) from Multiple Chloroplast and Nuclear DNAs - Wang, Yan; Chen, Qing; Chen, Tao; Tang, Haoru; Liu, Lin; Wang, Xiaorong (Frontiers in Plant Science, 2016)
Rubus L. is a large and taxonomically complex genus, species of which exhibit apomixis, polyploidy and frequent hybridization. Most of Chinese Rubus are assigned in two major sections, Idaeobatus and Malachobatus. To explore the phylogenetic relationships within Chinese Rubus, inferences upon three chloroplast DNA (rbcL, rpl20-rps12 and trnG-trnS), nuclear ribosomal ITS, and two low-copy nuclear markers (GBSSI-2 and PEPC) were deduced in 142 Rubus taxa from 17 subsections in 6 sections. nrITS and GBSSI-2 were the most informative among the six DNA regions assessed. Phylogenetic relationships within Rubus were well resolved by combined nuclear datasets rather than chloroplast markers. The phylogenetic inferences strongly supported that section Idaeobatus was a polyphyletic group with four distant clades. All samples of sect. Malachobatus formed a monophyletic clade, in which R. tsangorum and R. amphidasys of sect. Dalibardastrum, and R. peltatus from subsection Peltati of sect. Idaeobatus were always nested. Rubus pentagonus (2n = 2x = 14) from subsect. Alpestres of sect. Idaeobatus was a sister group to the polyploid sect. Malachobatus, as well as the polytomy of three sect. Cyalctis members. This suggests that some polyploids of Malachobatus might originate from common ancestors, via polyploidization of hybrids between R. pentagonus and sect. Cylactis species. They had experienced species explosion in a short time. Section Dalibardastrum species have potential parental lineages from subsects. Moluccani and Stipulosi of sect. Malachobatus. Based on molecular phylogenies, we also provided recommendations for the taxonomic treatments of four taxa. In addition, our results showed certain incongruence between chloroplast and nuclear markers, which might be due to hybridization and introgression.